Quiet Quitting: A Case Study of Silent Withdrawal Among University Lecturers - Suryanto Suryanto; Mohammad Fakhruddin Mudzakkir; Rifa’atul Maftuhah; Hetty Murdiyani; Ummi Masrufah Maulidiyah (Psikostudia : Jurnal Psikologi, 2026)
This study aims to explore the phenomenon of quiet quitting among university lecturers in the context of implementing the Tri Dharma of Higher Education through the lens of Social Exchange Theory. A qualitative case study approach was employed involving ten permanent lecturers from Muhammadiyah and Aisyiyah higher education institutions. Data were collected through semi-structured in-depth interviews and analyzed using qualitative content analysis. The findings indicate that teaching-centered workloads, multiple role demands, and administrative and personal responsibilities create an imbalance in the implementation of the Tri Dharma, particularly by reducing lecturers' engagement in research and community service. These conditions are further exacerbated by limited institutional support, leading lecturers to adopt coping strategies such as setting work boundaries, prioritizing tasks, and relying on collegial support to maintain their psychological well-being. The findings suggest that quiet quitting among lecturers should not be interpreted as a refusal to work, but rather as a form of selective withdrawal from discretionary activities beyond core teaching responsibilities due to an imbalance between job demands and organizational support. This study highlights that quiet quitting is shaped by the interaction of workload, role conflict, and the quality of reciprocal relationships between lecturers and their institutions. Therefore, higher education institutions should develop more balanced workload management systems and strengthen organizational support to enhance lecturers' engagement and well-being.Penelitian ini bertujuan untuk mengeksplorasi fenomena quiet quitting di kalangan dosen universitas dalam konteks pelaksanaan Tri Dharma Perguruan Tinggi melalui perspektif Social Exchange Theory. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus yang melibatkan sepuluh dosen tetap dari perguruan tinggi Muhammadiyah dan Aisyiyah. Data dikumpulkan melalui wawancara mendalam semi-terstruktur dan dianalisis menggunakan analisis konten kualitatif. Hasil penelitian menunjukkan bahwa beban mengajar yang dominan, tuntutan peran ganda, serta tanggung jawab administratif dan personal menyebabkan ketidakseimbangan pelaksanaan Tri Dharma, terutama berkurangnya keterlibatan dosen dalam penelitian dan pengabdian kepada masyarakat. Kondisi tersebut diperkuat oleh keterbatasan dukungan institusional, sehingga dosen cenderung menerapkan strategi penyesuaian seperti menetapkan batasan kerja, memprioritaskan tugas, dan mengandalkan dukungan kolegial untuk mempertahankan kesejahteraan psikologis. Temuan ini menunjukkan bahwa quiet quitting pada dosen tidak dimaknai sebagai penolakan terhadap pekerjaan, melainkan sebagai bentuk penarikan diri secara selektif dari aktivitas yang bersifat di luar kewajiban utama akibat ketidakseimbangan antara tuntutan kerja dan dukungan organisasi. Penelitian ini menegaskan bahwa fenomena quiet quitting dipengaruhi oleh interaksi antara beban kerja, konflik peran, dan kualitas hubungan timbal balik antara dosen dan institusi. Oleh karena itu, perguruan tinggi perlu mengembangkan sistem pengelolaan beban kerja yang lebih proporsional serta memperkuat dukungan organisasi untuk meningkatkan keterlibatan dan kesejahteraan dosen.